Detection of volume alterations in hippocampal subfields of rats under chronic unpredictable mild stress using 7T MRI: A follow‐up study. Issue 5 (22nd February 2017) - Li, Yuefeng; Zhu, Xiaolan; Ju, Shenghong; Yan, Jinchuan; Wang, Dongqing; Zhu, Yan; Zang, Fengchao
Abstract : Purpose: To determine hippocampal subfields volume loss in depression, which was simulated by a rat chronic unpredictable mild stress (CUMS) model. As different cellular and molecular characteristics in hippocampal subfields, these subfields are regarded as differentially vulnerable to processes associated with stress. Materials and Methods: Twenty male Wistar rats were exposed to various stressors until the model was successfully established. The effects of physical exercise on recovery of hippocampal volume in depressed rats were simulated using the wheel running test (WRT). These rats hippocampal volumes were dynamically measured using T 2 ‐weighted images ( T 2 WIs) at 7T structural magnetic resonance imaging (MRI). Results: After 4 weeks of CUMS (CUMS‐4W), the behavioral tests showed that the rat model of depression was successfully established ( P < 0.001). In this process, the bilateral CA1 volume was significantly atrophic after 2 weeks of CUMS (CUMS‐2W) compared with controls (left: 21.09 ± 2.31 vs. 26.16 ± 3.83 mm 3, P < 0.001; right: 21.05 ± 2.36 vs. 26.12 ± 3.78 mm 3, P < 0.001), whereas the other subfields did not show a similar change (all P > 0.05). The volume of CA3, dentate gyrus (DG), and subiculum displayed atrophy after CUMS‐4W (CA3: left:12.23 ± 1.10 mm 3, right: 12.20 ± 1.14 mm 3 ; DG: left:8.16 ± 0.58 mm 3, right: 8.18 ± 0.92 mm 3 ; subiculum: left: 4.30 ± 0.52 mm 3, right: 4.29 ± 0.44 mm 3 ; all P < 0.05). The rats' (CUMS‐4W) hippocampal DG volume was restored (left: 10.67 ± 1.60 mm 3, right: 10.71 ± 1.58 mm 3 ), and the depression‐like behaviors of these rats improved after WRT‐4W ( P < 0.05). Conclusion: In general, volume loss was demonstrated in various rat hippocampal subfields during the development and recovery from depression, which were detected by ultrahigh‐field MRI. Level of Evidence: 3 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2017;46:1456–1463.